Protection of Messenger RNA Vaccines Against Hospitalized Coronavirus Disease 2019 in Adults Over the First Year Following Authorization in the United States. (9th July 2022) - Tenforde, Mark W; Self, Wesley H; Zhu, Yuwei; Naioti, Eric A; Gaglani, Manjusha; Ginde, Adit A; Jensen, Kelly; Talbot, H Keipp; Casey, Jonathan D; Mohr, Nicholas M; Zepeski, Anne; McNeal, Tresa; et al.
Abstract: Background: Coronavirus disease 2019 (COVID-19) messenger RNA (mRNA) vaccines were authorized in the United States in December 2020. Although vaccine effectiveness (VE) against mild infection declines markedly after several months, limited understanding exists on the long-term durability of protection against COVID-19–associated hospitalization. Methods: Case-control analysis of adults (≥18 years) hospitalized at 21 hospitals in 18 states 11 March–15 December 2021, including COVID-19 case patients and reverse transcriptase-polymerase chain reaction–negative controls. We included adults who were unvaccinated or vaccinated with 2 doses of a mRNA vaccine before the date of illness onset. VE over time was assessed using logistic regression comparing odds of vaccination in cases versus controls, adjusting for confounders. Models included dichotomous time (<180 vs ≥180 days since dose 2) and continuous time modeled using restricted cubic splines. Results: A total of 10 078 patients were included, 4906 cases (23% vaccinated) and 5172 controls (62% vaccinated). Median age was 60 years (interquartile range, 46–70), 56% were non-Hispanic White, and 81% had ≥1 medical condition. Among immunocompetent adults, VE <180 days was 90% (95% confidence interval [CI], 88–91) versus 82% (95% CI, 79–85) at ≥180 days ( P < .001). VE declined for Pfizer-BioNTech (88% to 79%, P < .001) and Moderna (93% to 87%, P < .001) products, for younger adults (18–64 years) (91% to 87%, P = .005), and for adults ≥65 years of age (87% to 78%, P < .001). In models using restricted cubic splines, similar changes were observed. Conclusions: In a period largely predating Omicron variant circulation, effectiveness of 2 mRNA doses against COVID-19–associated hospitalization was largely sustained through 9 months. Abstract : Among 10 078 adults hospitalized at 21 centers March–December 2021, 2-dose coronavirus disease 2019 (COVID-19) messenger RNA vaccine effectiveness (VE) in immunocompetent patients decreased from 90% to 82% at <180 days and ≥180 days. VE against severe COVID-19 was largely sustained >6 months postvaccination.